2021
DOI: 10.3389/fpsyt.2021.690903
|View full text |Cite
|
Sign up to set email alerts
|

The Interpersonal-Psychological Theory of Suicide to Explain Suicidal Risk in Eating Disorders: A Mini-Review

Abstract: Suicide is a major cause of death in Eating Disorders (EDs) and particularly in anorexia nervosa (AN). The aim of the present mini-review was to summarize the literature focusing on the interpersonal-psychological theory of suicide (IPTS) by Thomas E. Joiner, as applied to explain suicidal risk in EDs. PubMed database was used to search articles focused on IPTS in EDs; 10 studies were eventually included. The majority of the included studies reported data from the same sample, even though the hypotheses and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
3
0
6
Order By: Relevance
“…Hopelessness has been strongly linked to a lack of 'belongingness' (i.e., disrupted relationships/isolation) (Lineham & Nielsen, 1981). These conclusions fit relatively well with Klonsky and May's (2015) framework of four key contributors to suicidality: physical and emotional/psychological pain (PTSD), hopelessness (including powerlessness/helplessness), lack of connectedness (disrupted relationships and isolation), and suicide capability (the means to take one's own life) Added to this has been 'burdensomeness' (Zeppegno, 2021), which is associated with self-hatred (Van Ziegler, 2003;Chang et al, 2014). There is a link between individuals having less self-compassion, feeling less belongingness, and experiencing a higher level of burdensomeness; and these factors were associated with increased depressive symptoms (Øverup et al, 2017).…”
Section: Rapid Review Summarysupporting
confidence: 59%
See 1 more Smart Citation
“…Hopelessness has been strongly linked to a lack of 'belongingness' (i.e., disrupted relationships/isolation) (Lineham & Nielsen, 1981). These conclusions fit relatively well with Klonsky and May's (2015) framework of four key contributors to suicidality: physical and emotional/psychological pain (PTSD), hopelessness (including powerlessness/helplessness), lack of connectedness (disrupted relationships and isolation), and suicide capability (the means to take one's own life) Added to this has been 'burdensomeness' (Zeppegno, 2021), which is associated with self-hatred (Van Ziegler, 2003;Chang et al, 2014). There is a link between individuals having less self-compassion, feeling less belongingness, and experiencing a higher level of burdensomeness; and these factors were associated with increased depressive symptoms (Øverup et al, 2017).…”
Section: Rapid Review Summarysupporting
confidence: 59%
“…This suggests disruption in their relationships, distance (or complete isolation) from supportive others, and a lack of belongingness -a finding reflected throughout a wide range of the literature on the antecedents of suicide. Zeppegno et al (2021) found that feeling burdensome is also significantly correlated with suicidality, including in eating disordered patients, especially those with anorexia (in relation to which symptoms might represent anger and hatred towards the self). In support of the latter perspective, Yen and Siegler (2003) and Chang et al (2014) found that forgiveness of self/ alleviating feelings of self-blame and promoting the motivation to change reduced or eliminated the positive link between domestic abuse and suicidality.…”
Section: Co-morbid Depression and Ptsdmentioning
confidence: 97%
“…Одним из признаков депрессии у больных с ИБС является высокая гипергнозия, то есть повышенная субъективная значимость переживаний телесного неблагополучия. Чаще всего такие больные жалуются на боли в области сердца, которые не соответствуют тяжести объективной соматической патологии, а также с трудом купируются препаратами [11].…”
Section: материалы и методыunclassified
“…Consequently, individuals direct anger at themselves through ED symptomatology. Related to this, individuals’ expression of anger toward themselves in the form of non-suicidal self-injury and self-injury attempts are frequent among those with EDs and are indicative of increased eating pathology ( 27 , 28 ). Therefore, inhibited expression of negative emotions is related to cognitive and affective components of body image dissatisfaction ( 21 , 29 ).…”
Section: Introductionmentioning
confidence: 99%